SENGKETA TANAH WARIS YANG DIKUASAI MELAWAN HUKUM (Studi Kasus Putusan No. 299/PDT.G/2014/PN.JKT.PST) - Vernando Vernando (Jurnal Ilmu Hukum, 2019)
AbstractIt starts when the Plaintiff intends to see the object land of the dispute. They were very surprised that the inheritance land owned by the Plaintiff was seized and controlled by the Defendant without permission from the legal heirs of the landowners. By setting up a semi-permanent building wildly. The Defendant does not have an official land certificate and a valid building permit. The Plaintiff wanted to settle well in family terms. But the good intentions of the Plaintiff were not responded positively by the Defendant. To free the land of the object of the dispute, the Plaintiff filed a lawsuit to the District Court. The Plaintiff's lawsuit was granted by the judge. Feeling dissatisfied, the Defendant, who is now a Plaintiff, filed a lawsuit back to the Court repeatedly to be able to occupy the object land for a longer dispute. However, it is fitting for the claim filed by the Plaintiff to be accepted on the grounds that the claim is in accordance with the strong evidence that has been submitted. Where the Defendant cannot show strong evidence in the Court and does not have the correct legal reasons. Then the actions taken by the Defendant are stated as illegal acts as stated in Article 1365 of the Civil Cod. This research is expected can analyze the problems that occur during the implementation of a claim called the plaintiff against the defendant about acts that are against the law against the land dispute under control. So the results are expected to solve the problem of land disputes where a way out is found in solving cases related to land disputes for those engaged in agrarian law.Keywords: Certificate of ownership, Land Dispute, Against Law.AbstrakBerawal ketika Penggugat bermaksud ingin melihat tanah objek sengketa. Mereka sangat terkejut tanah warisan yang dimiliki Penggugat diserobot dan dikuasai Tergugat tanpa ijin dari ahli waris pemilik tanah yang sah. Dengan cara mendirikan bangunan semi permanen secara liar. Tergugat tidak memiliki sertifikat tanah yang resmi dan surat ijin mendirikan bangunan yang sah. Penggugat ingin menyelesaikan baik-baik secara kekeluargaan.Tapi niat baik Penggugat tidak direspon secara positif oleh Tergugat. Untuk membebaskan tanah objek sengketanya, Penggugat melayangkan gugatannya ke Pengadilan Negeri. Gugatan Penggugat dikabulkan oleh hakim. Merasa tidak puas Tergugat dahulu yang sekarang menjadi Penggugat mengajukan gugatan kembali ke Pengadilan berulang kali agar dapat menempati tanah objek sengketa lebih lama. Namun sudah sepatutnya gugatan yang diajukan Penggugat diterima dengan alasan gugatan sudah sesuai dengan bukti-bukti yang kuat yang tela diajukan. Dimana Tergugat tidak dapat menunjukkan bukti yang kuat di Pengadilan dan tidak mempunyai alasan hukum yang benar. Maka tindakan yang dilakukan Tergugat dinyatakan sebagai perbuatan melawan hukum seperti yang dinyatakan pada Pasal 1365 KUHPerdata. Penelitian ini adalah penelitian yuridis normatif yang menggunakan bahan pustaka dan data sekunder. Diharapkan  melalui penelitian ini dapat menganalisis masalah-masalah yang terjadi pada saat pelaksanaan gugatan yang diajukan penggugat terhadap tergugat tentang perbuatan yang melawan hukum terhadap sengketa tanah yang dikuasai. Sehingga hasilnya diharapkan dapat memecahkan persoalan sengketa tanah dimana didapat jalan keluar dalam memecahkan kasus terkait sengketa tanah bagi yang berkecimpung dibidang hukum agraria.Kata Kunci : Sertifikat Hak Milik, Sengketa Tanah, Melawan Hukum.